The influence of brand image, service quality, service convenience, and product innovation on repurchase intention at Ace Hardware in Jabodetabek - Tafarel, Aldo; Ginting, Ari Mulianta (Enrichment : Journal of Management, 2025)
This study aims to explore the factors influencing repurchase intention among Ace Hardware customers in Jabodetabek by integrating service quality, service convenience, brand image, and product innovation as independent variables, with customer satisfaction as a mediating variable. The research employs a quantitative method with a survey approach involving 235 respondents selected through purposive sampling. Data were collected using a questionnaire with a 5-point Likert scale and analyzed using PLS-SEM method. The results of the study indicate that the independent variables, service quality also service convenience, have a significant effect on customer satisfaction, which subsequently acts as a mediator in the relationship with repurchase intention. Additionally, brand image, and product innovation, also directly influence repurchase intention. By enhancing all independent variable either through customer satisfaction or directly, repurchase intention can be significantly increased. Therefore, this study provides practical insights for Ace Hardware to develop marketing and operational strategies focused on boosting repurchase intention in Ace Hardware stores in Jabodetabek